In Vitro Culture of Orchids Grammatophyllum scriptum lindl. from Ambonese banana Peel in Foliar Fertilizer Medium - Etty Handayani; Agung Astuti; Yogawati Printarani Yahwidhi (Akademi Komunitas Perkebunan Yogyakarta, 2023)
The sustainability of Grammatophyllum scriptum orchids in nature is threatened due to excessive harvesting which results in changes and damage to the orchid's growing habitat. G. scriptum orchid is one of the endemic orchids that has uniqueness and high economic value. In vitro culture propagation of G. scriptum orchids is carried out to multiply and maintain the existence of the orchid. The use of alternative media in vitro culture is carried out to minimize the cost of making the medium and utilize materials available in nature. The utilization of Ambonese banana peel waste that has not been carried out optimally is considered to be one of the choices as an alternative medium in propagation of G. scriptum orchids This study aims to determine the most appropriate combination of foliar fertilizer and banana peel concentration for in vitro multiplication of orchid explants and to examine the effect of the combination of leaf fertilizer and banana peel concentration on the multiplication of orchid explantsVitro. The study will be carried out using a single-factor experimental method with 8 treatments, arranged according to the Complete Randomized Design (RAL). The treatment tried was in vitro culture of G. scriptum orchids on Growmore media and Ambonese banana peels including inner banana peels of 50g/L and 100g/L; outer banana peel 50 g/L and 100 g/L; banana peel combined 50 g / L and 100 g / L. The results showed the addition of Ambon banana peel had an influence on the percentage of life and growth of shoots, leaves and roots of G. scriptum orchid plants Treatment with the addition of a combined banana peel of 50 g / L in leaf fertilizer medium provides the best growth in terms of the percentage of life, plant height growth, leaves and plant roots.